2013
DOI: 10.1190/geo2012-0115.1
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Exploration using CSAMT data: Application to Longmen region metallogenic belt, Guangdong Province, China

Abstract: A controlled-source audio-frequency magnetotelluric (CSAMT) survey has been carried out to investigate potential iron (Fe) and polymetallic (Pb-Zn-Cu) deposits in Longmen region, which is one of the main metallogenic belts in southern China. Conducting geophysical surveys in this area is quite difficult due to mountainous terrain, dense forest, and thick vegetation cover. A total of 560 CSAMT soundings were recorded along twelve surveying lines. Two-dimensional Occam's inversion scheme was used to interpret th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Where AMT signal levels are low, e.g., in the dead band at $ 800-3000 Hz (Garcia and Jones 2002), the controlled-source audiomagnetotelluric method (CSAMT, f = 1-10000 Hz, Zonge and Hughes 1991) is routinely applied. Consequently, MT methods have a long-standing history in the investigation of mineral deposits (Strangway et al 1973;Meju 2002;Jones 2017) with field cases reported from, for instance, copper, gold, lead, silver and zinc deposits (Kellett et al 1993;Garcia Juanatey et al 2013a, b;Hübert et al 2013;Hu et al 2013), copper, gold and iron deposits (Heinson et al 2006), copper and iron deposits (Chouteau et al 1997;Jones and Garcia 2003), copper, iron and zinc deposits (Basokur et al 1997), copper, lead and zinc deposits (Sasaki et al 1992;Bastani et al 2009), copper and nickel deposits (Lakanen 1986;Livelybrooks et al 1996;Jones et al 1997;Balch et al 1998;Stevens and McNeice 1998;Zhang et al 1998;Watts and Balch 2000;King 2007;Xiao et al 2011;Varentsov et al 2013; Le et al 2016a), copper, silver and zinc deposits (Gordon 2007), gold deposits (Jones et al 1997;Liu et al 2006;Howe et al 2014;Takam Takougang et al 2015;Hübert et al 2016;Le et al 2016b), and uranium deposits (Leppin and Goldak 2005;Tuncer et al 2006;Farquharson and Craven 2009;Goldak et al 2010;…”
Section: Mt Methods In Exploring Deep Ore Depositsmentioning
confidence: 99%
“…Where AMT signal levels are low, e.g., in the dead band at $ 800-3000 Hz (Garcia and Jones 2002), the controlled-source audiomagnetotelluric method (CSAMT, f = 1-10000 Hz, Zonge and Hughes 1991) is routinely applied. Consequently, MT methods have a long-standing history in the investigation of mineral deposits (Strangway et al 1973;Meju 2002;Jones 2017) with field cases reported from, for instance, copper, gold, lead, silver and zinc deposits (Kellett et al 1993;Garcia Juanatey et al 2013a, b;Hübert et al 2013;Hu et al 2013), copper, gold and iron deposits (Heinson et al 2006), copper and iron deposits (Chouteau et al 1997;Jones and Garcia 2003), copper, iron and zinc deposits (Basokur et al 1997), copper, lead and zinc deposits (Sasaki et al 1992;Bastani et al 2009), copper and nickel deposits (Lakanen 1986;Livelybrooks et al 1996;Jones et al 1997;Balch et al 1998;Stevens and McNeice 1998;Zhang et al 1998;Watts and Balch 2000;King 2007;Xiao et al 2011;Varentsov et al 2013; Le et al 2016a), copper, silver and zinc deposits (Gordon 2007), gold deposits (Jones et al 1997;Liu et al 2006;Howe et al 2014;Takam Takougang et al 2015;Hübert et al 2016;Le et al 2016b), and uranium deposits (Leppin and Goldak 2005;Tuncer et al 2006;Farquharson and Craven 2009;Goldak et al 2010;…”
Section: Mt Methods In Exploring Deep Ore Depositsmentioning
confidence: 99%
“…To solve this problem, most geophysicists have used additional methods to confirm the existence of an interesting underground structure, such as fracture zones and a water reservoir rock (WRR) (e.g. He, 2018; Hu et al., 2013; Kouadio et al., 2020; Liu et al., 2023; Lubang et al., 2023; Parsekian et al., 2015). Although a combination of several methods used to supplement the CSAMT method is a good alternative in proposing a drilling location, some local geophysical companies have refrained from combining several methods to make profits and save time.…”
Section: Introductionmentioning
confidence: 99%
“…Xiao and Wang [12] used Bouguer gravity and aeromagnetic data to further understand the geological and mineral resources near the porphyry copper molybdenum polymetallic mineralization in the Tianshan area of China. Hu et al [13] explored potential iron and polymetallic lead-zinc-copper deposits in the Longmen area by the CSAMT method and found high-grade lead-zinc-silver-titanium ore through drilling based on inversion results. Guo et al [14] applied the CSAMT method to the exploration of the Jianshui lead-zinc mine and drew the underground resistivity distribution map through data processing and inversion.…”
Section: Introductionmentioning
confidence: 99%